Synthesis and Spectroscopic Characterization of New N4O4 Ligand and Its Transition Metal Ion Complexes with Ni(II), Zn(II) and Cd(II) - Al-Karkhi, Isam H T (Al-Nahrain Journal of Science, 2018)
A new tetrahedral ligand N'-(1-(2,4-dihydroxyphenyl)ethylidene)-2-hydroxybenzohydrazide (H2L) was synthesized by refluxing 1-(2,4-dihydroxyphenyl) ethanone with 2-hydroxybenzohydrazide. Three transition metal complexes with Cd+2, Ni+2 and Zn+2 were also synthesized with H2L. Characterization of all newly synthesized compounds was achieved using elemental analyses, mass spectroscopy, magnetic susceptibility, molar conductivity, UV–VIS, IR and 1HNMR, spectral studies. Studies indicate that the complexes are expected to exist in distorted octahedral shape and the ligand coordinates through azomethine nitrogen and two phenolicoxygen, in additionto the two water molecules.